Causal Effects of Addressing and PSI on Compliance with a Social Media Influencer’s Recommendations - Nyrhinen, Jussi; Rantala, Eero; Tuominen, Jesse; Makkonen, Markus; Wilska, Terhi-Anna; Frank, Lauri (38th Bled eConference: Empowering Transformation: Shaping Digital Futures for All: Conference Proceedings, 2025)
Our between-subjects experimental study on US citizens aged 18-35-years (n = 401) revealed that the young people are more likely to comply with recommendations by influencers who address the viewers of their YouTube videos. The viewers also experienced higher levels of parasocial interaction if an influencer addressed them verbally and physically in the video. The experience of parasocial interaction increased the likelihood to comply with the influencer’s recommendations. Our findings emphasize the role of humane and social factors in content marketing.